2006
DOI: 10.1055/s-2006-942530
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient C-C Bond-Forming Reactions of an α-Cyanoketene Dithioacetal with Aldehydes and Ketones

Abstract: In the presence of titanium(IV) chloride, the C-C bondforming reaction of the a-cyanoketene cyclic dithioacetal 1,3-dithiolan-2-ylideneacetonitrile with various aldehydes and ketones afforded multifunctional pentanedinitriles, 3-substituted-or 3,3-disubstituted 2,4-di-1,3-dithiolan-2-ylidenepentanedinitriles, respectively, in good to excellent yields under very mild conditions. A possible mechanism involving consecutive C-C bond formation was proposed.The C-C bond-forming reaction is a fundamental reaction for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…On the basis of all the results mentioned together with our previous reports, [14,16,17] a plausible mechanism for this new MCR is outlined in Scheme 2. …”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…On the basis of all the results mentioned together with our previous reports, [14,16,17] a plausible mechanism for this new MCR is outlined in Scheme 2. …”
Section: Resultsmentioning
confidence: 57%
“…By increasing H 2 SO 4 loading to 50 mol%, the reaction could reach completion rapidly within 5 h, furnishing 4a in excellent yield (93%, Table 1, entry 4). With lower amounts of aldehyde 2a (1.2 equiv, Table 1, entry 5) or sulfinic acid 3a (2.0 equiv, Table 1, entry 6), satisfactory yields (83% and 80%) were still obtained after a prolonged reaction time, but with the formation of undesired by-product A [14c, 16] in 8% and 12% yields, respectively. Next, other solvents instead of CH 3 CN were tested.…”
Section: Resultsmentioning
confidence: 99%
“…In our early research, the formation of C−C bond between α‐EWG ketenedithioacetals derivatives and various alcohols, aldehydes or ketones catalyzed by Lewis acid was reported . However, BF 3 ⋅ EtO 2 and TiCl 4 are so readily soluble in a multitude of solvents that they cannot be regenerated.…”
Section: Methodsmentioning
confidence: 99%
“…This finding was further studied by our group recently in order to show the potential of dithi(ol)anylium salts as an equivalent to ketene dithioacetals [24]. The disadvantages of the current synthetic use of ketene 1,3-dithioacetals are caused by the preparative effort for their isolation (via dithi(ol)anylium species) [25] and their substitution-dependent reactivity which often limits their use to ketenes with electron-withdrawing substituents in α-position [9,26]. Our recent approach to the synthesis of α-arylazo-carbonyl compounds showed that easily available dithi(ol)anylium tetrafluoroborates [2728] (following shortened to TFBs) serve as stable precursors for ketene dithioacetals [29].…”
Section: Introductionmentioning
confidence: 99%